Mytran: A Programming Language for Data Abstraction - Snider, Timothy West (My University, 1981)
This project is about the design and implementation of a new programming language, Mytran. Two new control statements are implemented in Mytran. Data abstraction is supported through parameterized types or "type constructors".
Keywords: Mytran, programming, language, data abstraction